2019
DOI: 10.3892/mmr.2019.9835
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone protects against arsanilic acid‑induced rat vestibular dysfunction through the BDNF and JNK 1/2 signaling pathways

Abstract: The brain-derived neurotrophic factor (BDNF) and c-Jun NH 2-terminal kinase (JNK) signaling pathways are therapeutic targets to prevent degeneration in the central nervous system. Dexamethasone (DXMS), a glucocorticoid, protects against vestibular brain injury, however, the molecular mechanisms have yet to be fully elucidated. To investigate whether the BDNF and JNK signaling pathways are involved in the protective effects of DXMS in rats with vestibular dysfunction, a rat model of severe vestibular deficits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…At the same time, GCs’ effects on normal brain tissue remain less studied. It has been shown that dexamethasone (DXM) induces the plasticity of neurons, Schwann cells, oligodendrocytes, astrocytes, and microglia [ 12 ] and possesses a neuroprotective effect against brain vestibular damage [ 13 ] and neurodegeneration [ 10 ].Although, according to the other study, DXM has no effect on normal white matter cells in the contralateral hemisphere of the brain in tumor patients in vivo [ 14 ]. Most of the described mechanisms are mainly related to the intrinsic properties of normal or glioma cells, whereas GCs’ effects on the brain extracellular matrix (ECM) are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, GCs’ effects on normal brain tissue remain less studied. It has been shown that dexamethasone (DXM) induces the plasticity of neurons, Schwann cells, oligodendrocytes, astrocytes, and microglia [ 12 ] and possesses a neuroprotective effect against brain vestibular damage [ 13 ] and neurodegeneration [ 10 ].Although, according to the other study, DXM has no effect on normal white matter cells in the contralateral hemisphere of the brain in tumor patients in vivo [ 14 ]. Most of the described mechanisms are mainly related to the intrinsic properties of normal or glioma cells, whereas GCs’ effects on the brain extracellular matrix (ECM) are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%